2021
DOI: 10.1097/gox.0000000000003817
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Chest Wall: A Tool for Advanced Microsurgical Training Simulating Depth and Limited View

Abstract: Summary: The deep inferior epigastric perforator (DIEP) flap has become the free flap of choice for autologous breast reconstruction. However, anastomoses of DIEP pedicles to internal mammary vessels in the chest wall are difficult due to restricted access and the depth of the vessels. Successful performance of such demanding procedures necessitates advanced requirements for microsurgical training models. The current chicken thigh model has been used to acquire microsurgical skills, allowing early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The tasks in these 10 steps were accomplished using various models involving latex materials, pig vessels, and living rat vessels. Although several articles have emphasized single constraint for microsurgical training (e.g., a microsurgical space restrictor was reported by Wang et al 13 and a three-dimensional printed rib cage device was presented by Papavasiliou et al 14 ), there is no microsurgical training device on the market that can comprehensively simulate various clinical real-world scenarios. The aim of our training program was to accommodate changeable and complicated operative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The tasks in these 10 steps were accomplished using various models involving latex materials, pig vessels, and living rat vessels. Although several articles have emphasized single constraint for microsurgical training (e.g., a microsurgical space restrictor was reported by Wang et al 13 and a three-dimensional printed rib cage device was presented by Papavasiliou et al 14 ), there is no microsurgical training device on the market that can comprehensively simulate various clinical real-world scenarios. The aim of our training program was to accommodate changeable and complicated operative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this system's reliance on cabled leads connected to a control unit can be cumbersome, restrictive, and uncomfortable for patients [58] . These systems are also known to trigger false alarms due to many inevitable factors such as patient movement [59] . Addressing these challenges, the novel ViOptix Intra.Ox handheld device was developed for more accurate and portable assessments.…”
Section: Advanced Tissue Oximetry Technologymentioning
confidence: 99%
“…Mehta et al applied 3D printing to autologous reconstructive breast surgery by creating a patient-specific model that helped teach DIEP flap breast reconstruction to trainee surgeons who used the model preoperatively and postoperatively to visualize the intramuscular path of the deep inferior epigastric perforator vessels [ 56 ]. Papavasiliou et al developed a 3D printed chest wall as an adjunct to the current chicken thigh model that mimics the anastomosis performed during DIEP breast reconstruction, representing a simple and cost-effective enhancement that provides a significantly more realistic resemblance to a clinical situation than the original model [ 98 ]. Lastly, Lim et al reported the use of a novel simulator with different breast volumes and ptosis grades in a single model for teaching marking in oncoplastic surgery [ 99 ].…”
Section: Three-dimensional Printing As An Educational Toolmentioning
confidence: 99%